Anti-FGM agendas in Guinea-Bissau or the female body as a banner for human rights - Carvalho, C. (EASA-MAN Conference, 2017)
Anti-FGM agendas in Guinea-Bissau or the female body as a banner for human rights., comunicação Embodying the cultural difference: FGM/C and public policies, EASA-MAN Conference, P07, Lisboa, Instituto de Ciências Sociais, 5-7 julh